Analyze a Temperature and MHD Peristaltic Flow of Jeffrey Fluid through a Porous Wavechannel in a Rotating Frame - Al-Khafajy, Dheia G. Salih; Al-Kelabiy , Anaam Mahdi Abbas (Iraqi Journal of Science, 2024)
The aim of this paper is to analyse the temperature and magnetohydrodynamic (MHD) peristaltic flow of Jeffrey fluid through a porous wave channel under the influence of rotation. The study is in Cartesian coordinates, the system of equations governing this issue is nonlinear and non-homogeneous partial differential. For the purpose of solving this system, we assumed a short wavelength and a very low Reynolds number due to the flow channel structure. After obtaining the system solution, we used the Mathematica 13 program to analyse the results through graphs. It observed that the rotation,  magnetic field, viscosity and density of the fluid have an effective effect on the fluid movement and its temperature.